Anti-brain cholinergic auto antibodies from primary Sjögren syndrome sera modify simultaneously cerebral nitric oxide and prostaglandin biosynthesis - Orman, Betina (2007)
The presence of circulating antibodies from primary Sjögren Syndrome (pSS) patients enable to interact with rat cerebral frontal cortex by activating muscarinic acetylcholine receptors (mAChR). ELISA assay for PGE2 generation, nitric oxide synthase (NOS) activity was measured in cerebral frontal cortex slices by production of [U-14C]-citruline and mRNA isolation/quantitative PCR for COX-1 and COX-2 gene expression were carried out. By ELISA assay, it was shown that IgG from pSS patients reacted to cerebral frontal cortex cell surface and with human M1 and M3 mAChR. Beside pSS IgG displayed an agonistic-like activity stimulating NOS activity and PGE2 production associated with an increased COX-1 mRNA gene expression, without affecting COX-2 mRNA levels. Inhibition of phospholipase A2 (PLA2) and NOS prevented pSS IgG effects upon both PGE2 production and COX-1 mRNA levels. The results support the notion that serum IgG auto antibodies in pSS patients target cerebral mAChR may have pathogenic role in immune neuroinflammation and on cognitive dysfunction present in pSS patients.